Documents of the Ad Hoc Comitee on investigation of crimes of bolsheviks under Commander-in-Chief of Armed forces of the South of Russia as a source for the history of Russian Orthodox Church - Yulia Biryukova (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
This article provides analysis of reliability and value of documents accumulated by the Ad Hoc Committee on Investigation of Crimes of Bolsheviks under the Commander-in-Chief of the Armed Forces in the South of Russia. This analysis includes the study of documents of the Committee as a source for the Church history in the South of Russia, the study of periodicals and memoirs as well the study of the history of the original owner of the documents mentioned above. The Committee on Investigation of Crimes of Bolsheviks was founded on December 31, 1918 with the purpose of forming public opinion about the true nature of Bolsheviks’ power and the purpose of justifying the mission of the White. The aim of the Committee was of course not to carry out investigation in the fi rst hand, but to record crimes of Bolsheviks and then to inform the public, i.e. to use them as means of propaganda. However, this does not depreciate their value and validity because the work was conducted by the best professional experts in the fi eld of forensic medicine and law who strictly followed guidelines of the judicial proceedings, legal norms and principles. In addition, the work was done in the presence of foreign observers. The Committee was interested in obtaining true and authentic information since fabricated evidence would have lost its value. Investigation of the persecution of the Church in the Southern part of Russia was one of the Committee’s focal points. Materials which were collected by the Committee on the Area of Don Army and brought out with the help of the separate Don Branch Committee as a result of cooperation with diocesan bodies and local judicial departments are of special value.